ANALYSIS QUALITY CONTROL OF PRODUCT DEGAN SK 150 ML USING STATISTICAL QUALITY CONTROL (SQC) AT PT PRIMA KEMASINDO - Widyananda Fitrianoer Insani; Fahriza Nurul Azizah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
Products Degan SK 150 ml is a beverage product that is most in demand by consumers and is a coconut juice drink or nata. PT Prima Kemasindo always strives to maintain the quality of its products, especially the Degan SK 150 ml product. However, there are still products that do not meet the standards set by the company. This is because the company has not used a definite method to monitor the control limits for the level of product damage. Thus, this study aims to determine the limits of damage control and the level of damage that occurs, the factors that cause product damage and its consequences, as well as suggestions that can be given to improve product quality. The research method used is Statistical Quality Control (SQC) with p-chart, pareto diagrams, and fishbone diagrams. The result showed that the level of damage of Degan SK 150 ml product was beyond the control limit and there were five types of damage that often occurred during the January-March 2021 period caused by human factors, methods, and machines. Thus, there are seven proposed improvements given to the company in order to reduce the level of product damage.